The Determination of a Migration Wave Using Ethnicity and Community Ties - Lilo Locher (Institute for the Study of Labor (IZA), 2001)
If people come to live in a country different from their nation state, due to border shifts, expulsion, or migration, they adopt some of the new country?s habits after some time. This paper investigates their (return) migration decision when they have been restricted to live in the foreign country for some time and suddenly become free to return to the country of their original nationality. In our model, the population is located in small communities on a Hotelling line. The two poles represent the two nationalities. Utility depends on distance to the pole and to the center of the community someone is living in. Looking at ethnic German migration in the 1990s, we compare basic features of the migration wave with assumptions of the model, compare actual and predicted migration waves and discuss the impact of immigration restrictions.
Keywords: H11; H79; J11; J15; R23; F22; 330; Migration decision; migration networks; Hotelling model; ethnic Germans; Migrationstheorie; Standorttheorie; Hotelling Modell; Soziales Netzwerk; Ethnische Gruppe; Aussiedler; Schätzung; Theorie; Deutschland